Digital Democracy: Exploring the Potential and Challenges of SIPOL in the 2024 Indonesian Election - Febrianto Adi Saputro (Borong Newinera Publisher, 2024)
This research discusses the use of the SIPOL application as a form of digital transformation carried out by the KPU in the registration process as a candidate for the 2024 Election. The use of SIPOL for preparation for the 2024 Election is the second year it has been used. Previously, SIPOL was also used in 2017 to prepare for the 2019 Election. As a result, this research found that the use of SIPOL for the 2024 Election was better than the use of SIPOL for the 2019 Election. It was also found that the use of SIPOL aims to increase public participation in the 2024 elections. Additionally, SIPOL contributes to transparent and accountable elections. However, in its implementation, researchers found that the use of SIPOL still encountered many problems, for example the recording of a person's Population Identification Number (NIK) by a political party to be registered as a party member. Furthermore, some political parties still faced challenges in accessing SIPOL. SIPOL is also considered to be unable to help the public monitor political parties in fulfilling the requirements regulated by law. This research aims to explain the application of SIPOL in the registration stages of candidate participants in the 2024 election and to identify opportunities and challenges associated with using the SIPOL application. This research uses a qualitative descriptive analysis method. Data collection was carried out through the interview method accompanied by literature analysis and reporting in online media.